Speaking skill of elementary students reviewed by gender - Elnida Saldaria; Vina Anggia Nastitie Ariawan; Isah Cahyani (Asosiasi Dosen PGSD dan Dikdas Indonesia, 2019)
Speaking skill is one of language skill that used on daily life. Speaking skill include two aspects namely linguistic aspect and non-linguistic aspect. However, not all people have good speaking skill when facing some situation. That condition is available to students on language learning. Every students has difference obstacles on speaking. The obstacles of students’ speaking skill can be identified by speaking aspects. This research aims to identifying gender difference of students’ speaking skill on elementary schools. This research was using quantitative design within expost facto method. Technique of collecting sample used stratified sampling. Samples of this research were 30 students of third grade at one of elementary schools on Kampar Sub-District. Technique of collecting data in this research used speaking test. Technique of validity data used content validity and the validity was done by an expert or obtain expert judgement. Meanwhile, the data analysis used inference statistic. The result of this research useful to identify students’ speaking skill so teacher can give appropriate treatment to improve students’ speaking skill based on their necessities.